Surgical Site Infections Following Spine Surgery: Eliminating the Controversies in the Diagnosis - Chahoud, Jad; Kanafani, Zeina; Kanj, Souha S. (Frontiers in Medicine, 2014)
Surgical site infection (SSI) following spine surgery is a dreaded complication with significant morbidity and economic burden. SSIs following spine surgery can be superficial, characterized by obvious wound drainage, or deep-seated with a healed wound. Staphylococcus aureus remains the principal causal agent. There are certain pre-operative risk factors that increase the risk of SSI, mainly diabetes, smoking, steroids, and peri-operative transfusions. Additionally, intra-operative risk factors include surgical invasiveness, type of fusion, implant use, and traditional instead of minimally invasive approach. A high level of suspicion is crucial to attaining an early definitive diagnosis and initiating appropriate management. The most common presenting symptom is back pain, usually manifesting 2 to 4 weeks and up to 3 months after a spinal procedure. Scheduling a follow-up visit between weeks 2 to 4 after surgery is therefore necessary for early detection. Inflammatory markers are important diagnostic tools, and comparing pre-operative with post-operative levels should be done when suspecting SSIs following spine surgery. Particularly, Serum Amyloid A (SAA) is a novel inflammatory marker that can expedite the diagnosis of SSIs. Magnetic resonance imaging remains the diagnostic modality of choice when suspecting a SSI following spine surgery. While 18F-fluorodeoxyglucose-positron emission tomography is not widely used, it may be useful in challenging cases. Despite their low yield, blood cultures should be collected before initiating antibiotic therapy. Samples from wound drainage should be sent for Gram stain and cultures. When there is a high clinical suspicion of SSI and in the absence of superficial wound drainage, CT guided aspiration of paraspinal collections is warranted. Unless the patient is hemodynamically compromised, antibiotics should be deferred until proper specimens for culture are secured.